Assessing the 2005 Czech Proposals for Pension Reform - Hemmings, Philip (OECD Economics Department Working Papers, 2006)
The Czech Republic faces one of the largest demographic challenges in the OECD area and making sure the public pension system is able to cope with rapid population ageing is important for long-term fiscal stability and social welfare. This paper assesses five proposals for pension reform made in late 2005 with a view to helping progress towards a final decision on reform. The proposals cover a wide range of options: only parametric change of the current pay-as-you-go (PAYG) system, systems combining a PAYG pension with a second-pillar (defined-contribution), a flat-rate pension and a system of notional accounts. The analysis uses OECD simulation models to compare the proposals in terms of fiscal sustainability, safety nets, early retirement incentives, diversification into private provision, simplicity and the pensions-earnings link. This Working Paper relates to the 2006 OECD Economic Survey of the Czech Republic (www.oecd.org/eco/surveys/czech)